A etnoornitologia como elemento de integração do conhecimento popular ao ensino de biologia - Rezende, Jardel Pedro de Oliveira (2024)
This research addresses ethno-ornithology in high school as a strategy to value popular knowledge and integrate it into the school curriculum. The central problem investigates how the inclusion of ethno-ornithological knowledge can enrich biology education, promoting a deeper understanding of local biodiversity and environmental conservation. The objective is to explore ethno-ornithology as a pedagogical tool to strengthen students' connection with their environment, encouraging interdisciplinary learning and respect for nature. The methodology adopted involved the application of didactic sequences based on ethno-ornithological knowledge, collected through participatory research in local communities. The results demonstrated that the ethno-ornithological approach in biology teaching favors the appreciation of traditional knowledge, stimulates students' scientific curiosity and promotes awareness of the importance of conserving birds and their habitats. It is concluded that the integration of ethnoornithology in biology teaching programs is essential for effective environmental education, capable of forming conscious citizens responsible for the preservation of natural and cultural heritage.